2006
DOI: 10.1002/jmri.20568
|View full text |Cite
|
Sign up to set email alerts
|

Combination of free‐breathing and breathhold steady‐state free precession magnetic resonance angiography for detection of coronary artery stenoses

Abstract: Purpose:To analyze the incremental diagnostic value of a combination of two approaches (free-breathing and breathhold) vs. the sole free-breathing approach to coronary magnetic resonance angiography (CMRA) for detection of significant stenoses. Materials and Methods:Thirty patients were consecutively included in this prospective trial. CMRA was performed on a 1.5-T MR scanner (Magnetom Sonata, Siemens) using a balanced steady-state free precession (SSFP) sequence during free-breathing (2.4 ϫ 0.9 ϫ 0.7 mm 3 ). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…The mean length of each coronary artery visualised in our study was longer than previously reported for 4-slice MSCT scanners [21] and electron beam CT [21,22] or magnetic resonance angiography [23][24][25][26][27]. The measured overall length of the coronary arteries was comparable to the results of previously published studies using 16-slice [15,20] and 64-slice scanners [28] (Table 3).…”
Section: Comparison With Other Studiessupporting
confidence: 86%
“…The mean length of each coronary artery visualised in our study was longer than previously reported for 4-slice MSCT scanners [21] and electron beam CT [21,22] or magnetic resonance angiography [23][24][25][26][27]. The measured overall length of the coronary arteries was comparable to the results of previously published studies using 16-slice [15,20] and 64-slice scanners [28] (Table 3).…”
Section: Comparison With Other Studiessupporting
confidence: 86%
“…At present, coronary MRA with steadystate free precession (SSFP) is regarded as an increasingly advantageous approach to coronary MRA with its relatively high signal-tonoise ratio and good ability to image the coronary arteries [2,12,13]. To our knowledge, there have been no studies assessing the diagnostic capability of coronary MRA with SSFP for the detection of coronary stenosis in patients with high calcium scores.…”
Section: Conclusion-coronarymentioning
confidence: 99%
“…A combination of the breathhold and free-breathing approaches may improve the success rate of coronary MRA. 23,24 A shortcoming of the volume-targeted approach is the limited coverage of the coronary tree for each acquisition, thus accurate volume planning is required. The mean lengths of LAD and RCA in this study are shorter than that of the studies by Bogaert 25 (72 ± 15 and 90 ± 31 mm, respectively) and Kefer 26 (66 ± 12 and 115 ± 28 mm, respectively).…”
mentioning
confidence: 99%